CONSTRUCTION PRINCIPLES OF ELECTROTECHNICAL COMPLEXES CONTROL SYSTEMS OF AGRICULTURAL PRODUCTION - Dudnyk, A.; Lysenko, V. (Енергетика і автоматика, 2016)
The results of construction principles research of automatic control systems of agricultural production, which are influenced by natural disturbances, in order to increase energy efficiency, resource conservation and productivity are shown.